Optimized perioperative management (fast-track, ERAS) to enhance postoperative recovery in elective colorectal surgery - Schwenk, Wolfgang (German Medical Science GMS Publishing House, 2022)
Aim: This manuscript provides information on the history, principles, and clinical results of Fast-track or ERAS concepts to optimize perioperative management (OPM).Methods: With the focus on elective colorectal surgery description of the OPM concept and its elements for with special attention to the prevention of infectious complications and clinical results compared to traditional care will be given using recent systematic literature reviews. Additionally, clinical results for other major abdominal procedures are given.Results: An optimized perioperative management protocol for elective colorectal resections will currently consist of 25 perioperative elements. These elements include the time from before hospital admission (patient education, screening, and treatment of possible risk factors like anemia, malnutrition, cessation of nicotine or alcohol abuse, optimizationcurrent systemic disease, physical prehabilitation, carbohydrate loading, adequate bowel preparation) to the preoperative period (shortened fasting, non-sedative premedication, prophylaxis of PONV and thromboembolic complications), intraoperative measures (systemic antibiotic prophylaxis, standardized anesthesia, normothermia and normovolemia, minimally invasive surgery, avoidance of drains and tubes) as well as postoperative actions (early oral feeding, enforced mobilization, early removal of a urinary catheter, stimulation of intestinal propulsion, control of hyperglycemia). Most of these elements are based on high-level evidence and will also have effects on the incidence of postoperative infectious complications.Conclusion: Optimized perioperative management should be mandatory for elective surgery today as it enhances postoperative patient recovery, reduces morbidity and infectious complications.